Antimicrobial Activity of Garlic Against Helicobacter pylori - Guzeldag1, Gulcihan; Aysun Mercimek1, Hatice; Matyar2, Fatih (Asian Journal of Chemistry, 2014)
This study shows that garlic extracts produce levels of inhibition to Helicobacter pylori similar to those of the commercial materials. The research described here represents an important starting point in the fight against Helicobacter diseases. The extracted material can be used by direct application and involves a simple and economical extraction procedure that avoids isolation or purification techniques.